Hubungan Antara Kepuasan Kerja Dengan Komitmen Pada Guru Perempuan - Budi, Yolanda Arista, Dr. Nisa Rachmah N.A., M.Si, Psi (2017)
Commitment is required in educational organizations because a highly committed teacher in a school organization will tend to have a professional attitude and uphold the agreed values. One of the factors that influence commitment is job satisfaction. This study aims to determine the relationship between job satisfaction with commitment, job satisfaction level, commitment level and effective contribution from job satisfaction to commitment.Researchers use quantitative methods to achieve the objectives of this study. Research subjects used in this study were female teachers in SMK Negeri 2 Surakarta, amounting to 70 female teachers. The sampling technique used is metode purposive sampling. The result of data analysis shows correlation value (r) equal to 0,633 with significance (p) = 0,000 (p <0,01).This shows there is a very significant positive relationship between job satisfaction with commitment.Based on the results of the analysis is known job satisfaction variable has empirical average (RE) of 92.97 and hypothetical average (RH) of 77.5 which means job satisfaction research subject is high. The commitment variable has an empirical average (RE) of 40.31 and a hypothetical average (RH) of 32.5 which means the commitment of the research subject is moderate. The effective contribution of job satisfaction is 40% of commitmentand there are still 60% other factors that affect commitment.The results showed that job satisfaction contributes to the commitment of female teachers.